First-Principles Modelling of the Properties of Graphene Modified with Fluorine Atoms - V. N. Mishchanka (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2023)
The results of modeling the properties of graphene modified with fluorine atoms are presented. The creation of modern semiconductor devices requires the introduction of new materials. Graphene is one of them that is of interest to researchers. The addition of fluorine, hydrogen, and other chemical elements to graphene makes it possible to create its modifications. On this basis, it is possible to develop semiconductor devices and devices with improved output characteristics. The basic characteristics of graphene modification with the use of fluorine atoms, namely, the band diagram, the dependences of the density of state (DOS parameter) of electrons and holes on the energy value, were obtained by first-principles modeling. The dependences of charge carrier mobility on temperature are determined for the iterative solution of the Boltzmann transport equation The dependences and parameters obtained for fluorinated graphene can serve as a basis for creating new heterostructural devices containing layers of modified graphene and other semiconductor materials.